2013
DOI: 10.3724/sp.j.1037.2012.00109
|View full text |Cite
|
Sign up to set email alerts
|

HYDROGEN STORAGE PROPERTIES OF ScMn<SUB>2</SUB> ALLOY

Abstract: ScMn 2 Ð Ú (AE) ¤× * 1)2) 1) 1)ªÎ ¼AE³ØÝ H(D) ÄÐ ¤ , ×Ô ÍÄ Ø; 100 kPa, 298 K , 1 mol ScMn2 §  ¢ 3.7 3.6 mol; ScMn2 ×Ü ¡ª µ AE¡ Õ, Ô ÛÞ Ü ÛAE, ËÚ H §£ Ç. ÝÎ ÛAEÛ § Ä ΔH ΔS -45 kJ/mol -80 J/(K•mol); ScMn2 ª 113 kPa Ä H2(D2) AEAE³ (Â) Ð Á³Ò JMA , ¤ 0.4,  ¸ÍÄØ (16±0.3) (19±1.7) kJ/mol, ÀÍÄØ ¹  ScMn2 ׳ ØÒÚH £ ; ÝÄ § Ä ª 639 K ج ª , ª ¸ÍÄØ (144±14) kJ/mol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Investigations of hydrogen interaction with Sc-containing intermetallic phases were limited to the studies of the hydrogen interaction with Laves type ScT 2 intermetallics (T= Fe, Co, Ni, Mn) [17][18][19]. These studies showed that hydrogen storage capacities and thermal stabilities of the Sc-containing Laves type hydrides are lower as compared to the RE-containing analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of hydrogen interaction with Sc-containing intermetallic phases were limited to the studies of the hydrogen interaction with Laves type ScT 2 intermetallics (T= Fe, Co, Ni, Mn) [17][18][19]. These studies showed that hydrogen storage capacities and thermal stabilities of the Sc-containing Laves type hydrides are lower as compared to the RE-containing analogues.…”
Section: Introductionmentioning
confidence: 99%